2017
DOI: 10.1002/14651858.cd004767.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for cutaneous molluscum contagiosum

Abstract: No single intervention has been shown to be convincingly effective in the treatment of molluscum contagiosum. We found moderate-quality evidence that topical 5% imiquimod was no more effective than vehicle in terms of clinical cure, but led to more application site reactions, and high-quality evidence that there was no difference between the treatments in terms of short-term improvement. However, high-quality evidence showed a similar number of general side effects in both groups. As the evidence found did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 90 publications
1
70
0
7
Order By: Relevance
“…At high concentrations, imiquimod induces apoptosis of tumor cells via the activation of Bcl-2 proteins and the caspase family [187]. Besides FDA approved indications, topical imiquimod has been used in the treatment of several infectious skin disorders (nonanagenital cutaneous warts [188], Molluscum Contagiosum [189], cutaneous leishmaniasis [190], etc. ), neoplastic (fungoid mycosis [191], vascular tumors [192], cutaneous metastases [193], etc.)…”
Section: Pyrimidine and Purine Base Derivativesmentioning
confidence: 99%
“…At high concentrations, imiquimod induces apoptosis of tumor cells via the activation of Bcl-2 proteins and the caspase family [187]. Besides FDA approved indications, topical imiquimod has been used in the treatment of several infectious skin disorders (nonanagenital cutaneous warts [188], Molluscum Contagiosum [189], cutaneous leishmaniasis [190], etc. ), neoplastic (fungoid mycosis [191], vascular tumors [192], cutaneous metastases [193], etc.)…”
Section: Pyrimidine and Purine Base Derivativesmentioning
confidence: 99%
“…43,44 Molluscum contagiosum A vast number of treatment options ranging from physical destruction to topical and systemic agents have been suggested for the management of molluscum contagiosum (MC); however, clear evidence supporting their use is generally missing (Cochrane review). 45 Though few small randomized controlled trials and observational data reported a benefit from the use of topical imiquimod in showed that imiquimod is not effective in the treatment of MC in children. After 18 weeks of treatment, these two trials showed that imiquimod was no more effective in clearing MC than was the vehicle-containing cream (24% vs. 26-28%).…”
Section: Cutaneous Infectionsmentioning
confidence: 99%
“…A previous systematic review by van der Wouden et al 10 acknowledged the paucity of quality evidence on which to make clinical decisions in treating MC; of note, the group endorsed expectant management of the disease due to the lack of robust data that addresses the physical destruction of lesions and drug safety. In this study, we demonstrated that the use of topical cantharidin was well-tolerated in a pediatric cohort, with no serious adverse events reported.…”
Section: Discussionmentioning
confidence: 99%